Optimasi Wireless Access Point Menggunakan Algoritma Genetika (Studi Kasus Gedung C Fakultas Teknik) - Muhammad Rasyidin Siregar; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Laying a good WI-FI system is required to optimize the received power level from the transmitter to receiver. Characteristic of the most influential in determining the performance of a WI-FI system is the power level value. This value can be used to determine the coverage are of a transmitter. The Genetic Algorithm is chosen because according to various references, it is considered a suitable algorithm for optimization related problems. This algorithm can find the best solution of various possible solutions quickly and efficiently than any other algorithm. This research will be doing optimization, by comparing the optimization result with the existing conditions. The purpose of optimization is to rearrange the access point position in order to generate efficient coverage and signal strength. Selected research location is on 1st floor of C building Engineering Faculty, University Riau. From existing condition on the 1st floor there are 5 access points with coverage area value of 29.71%, after optimization the coverage area value increased to 50.21% with signal strength between -75 dBm to -70 dBm.Keyword : Access Point, Genetic Algorithm, Coverage Area, WI-FI, Signal Strength.